High-resolution isotope stratigraphy of the Lower Devonian. - Ala, Davin. (University of Ottawa (Canada), 1996)
A new data set of 53 $\sp‡$Sr/$\sp†$Sr ratios for the Lower Devonian has been collected from well preserved, and stratigraphically well constrained, brachiopod shells from the Leon region in Spain, western Urals in Russia, Podolia in Ukraine and New York State in the United States. Multiple criteria, including trace element and stable isotope (C, O) analysis, scanning electron microscopy, cathodoluminescence and optical light microscopy, were used to determine the state of preservation of the samples. One hundred and ten samples were analysed for $\delta\sp $C, with the results ranging from $-$1.49 to 5.5$\perthous$ (VPDB). The carbon isotope trend through the Lower Devonian is characterized by a flat slope within ${\pm}1.5\perthous$ of the mean value. One hundred and ten samples were analysed for $\delta\sp $O, with results that ranged from $-$8.84 to ${-}1.89\perthous$ (VPDB). The oxygen isotope trend through the lower Devonian is flat, except for the New York State samples which fall ${\sim}2\perthous$ lighter, probably because of the ambient temperature of the coeval seawater. For $\sp‡$Sr/$\sp†$Sr, the new data set is continuous and consistent for all study areas and shows a decrease from 0.70882 to 0.70782 from the Pridoli to the Emsian/Eifelian boundary. The Lower Devonian trend also fits well with the previously published Middle Devonian data. In detail, a relatively stable $\sp‡$Sr/$\sp†$Sr ratio for the Lochkovian is followed by a rapid decrease through the Pragian, and by a period of short-term small oscillations $(2\times 10\sp{-4})$ in the Emsian and the Eifelian. The observed decline in $\sp‡$Sr throughout the Lower Devonian may suggest that the fraction of strontium derived from seawater/mantle interactions is on the increase through the Lower Devonian in relation to strontium derived from sialic sources such as weathering of the continents. Paleogeographic and biogeographic data for this time period suggest that the relative sea level in the Lower Devonian was rising, possibly due to increased spreading rates at MOR's, in accord with the observed strontium isotope trend. In terms of stratigraphic resolution, the slope of the $\sp‡$Sr/$\sp†$Sr curve for the Lochkovian is too flat to be of utility for correlation purposes. In contrast, the steep slope observed in the Pragian and steep short-term fluctuations found in the Emsian may provide stratigraphic resolution on the order of 1-2 Ma.
Keywords: Geochemistry.